Artículos de opinión y ensayismo. Un ejemplo del 11-S de González de Cardedal - Santamaría Suárez, Luisa (Estudios sobre el Mensaje Periodístico, 2002)
The author try to explain in a few words that the commentary that uses to publish the newspapers is an essay characterized as a doctrinal work or as a scientific spreading. This is something completely different of news. The news is the report of something that happens in the external world. Essay is a subjective lucubration without any external proyection till the moment that is published.
Keywords: Essay; opinion; meditations; reflexive discourse; scientific spreading